Designer Babydan Sempadan Bioteknologi Manusia: Analisis Perundangan Berdasarkan Maqasid Syariah Dan Liabiliti Jenayah - Nurul A'ini Zalizan; Hasnizam Hashim; Wan Abdul Fattah Wan Ismail; Mohamad Aniq Aiman Alias; Ahmad Syukran Baharuddin; Syaryanti Hussin; Baidar Mohammed Mohammed Hassan (2026)
Non-Indexed Publication